Efficacy of different treatment protocols for endometritis in Camelus dromedarius - Zaher, Hany Ahmed; Al-Fares, Abdullah F.; Mesalam, Ayman (Frontiers in Veterinary Science, 2023)
Endometritis is considered a significant cause of infertility problems in dromedary camels. This study aimed to compare the efficacy of different treatment protocols for endometritis in dromedary camels under Abu Dhabi Emirates’ conditions. A total of 112 dromedary she-camels with uterine infection were subjected to uterine swabbing for bacterial culture and received one of the following treatments: (i) uterine douching with lotagen every other day for three doses, (ii) single parenteral oxytetracycline injection, (iii) subcutaneous injection with ceftiofur for five days, or (vi) combined oxytetracycline-ceftiofur injection. The results showed that Escherichia coli was the most isolated bacteria, followed by Streptococcus species. Treatment efficacy was (P < 0.05) higher in ceftiofur and oxytetracycline-ceftiofur protocols compared with lotagen and oxytetracycline protocols. The fertility indexes, services per conception and pregnancy rate, were improved in ceftiofur and mixed oxytetracycline plus ceftiofur protocols as the pregnancy rate was (P < 0.05) higher in those protocols compared with lotagen and oxytetracycline protocols (71.4% and 67.9% vs 39.3% and 42.9%, respectively). On the other hand, the number of services per conception was significantly lower in ceftiofur and oxytetracycline-ceftiofur protocols (1.2 for each protocol) than in lotagen and oxytetracycline protocols (1.8 and 1.7, respectively). In conclusion, subcutaneous injection of 1 ml ceftiofur per 50 kg body mass for five days can be used as an efficient treatment for uterine infection in female dromedary camels caused by E Coli and Streptococcus species for improving their fertility indexes.